Urbanization the Eastern Borders of Old Europe - Videiko, Mykhailo (Archaeologia Lituana, 2022)
Maria Gimbutas created an impressive picture of Old Europe, using, among others, materials from Trypillia Culture. From the very beginning, she took into account new archaeological discoveries from the 70s of the 20th century, namely, information about the large settlements. But fifty years ago, their studies were just beginning and this topic was not particularly popular among researchers outside of Ukraine. Today, news about life on the eastern borders of Old Europe, where these megasites, appeared more than 6000 years ago, appeares on the pages of leading archaeological publications and becomes the subject of discussions among archaeologists from different countries.